Market Research Analysis of Applied Technology in Shallot Retail Traders - Alfiana, Alfiana; Finahari, Nurida (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Retailers are the lowest level traders in the marketing distribution channel . They are identified as agents who act as â€˜product delivery peopleâ€™, without making product modifications . Their main activity is taking merchandise from distributors, sold directly in small packages. Shallot retailers also experience the same stigma, even though their products characteristics require special handling to prevent rotting before being sold. So far, the technology need for shallot products is considered only by farmers and large distributors. A preliminary market research has been conducted on a limited basis to see the need for shallot processing technology at the retail trader level. The research method used a G-Form-based questionnaire distributed to the shallot trader community, or filled out by surveyors during direct interviews. The research results showed that 4% of respondents stated that they needed appropriate technology, in form of drying machine, with 5 kg/hour maximum capacity, electric drive, and maximum price of around 5 million rupiah. The respondents majority Â (95%) seemed to state that they did not have procurement funds. It is predicted that 80-96% of respondents need the drying machine. This shows that there is a market opportunity for the technology, small scale, for shallot retailers in particular.